Pengalaman Flow dalam Belajar - Lucky Purwantini (Universitas Andalas, 2017)
Flow is a condition when individual merges within his/her activity. When a person in flow state, he/she can develop his/her abilities and more success in learning. The purpose of the study is to understand flow experience in learning among undergraduate student. The study used case study qualitative approach. Informant of this research was an undergraduate student which had flow experience. Data was collected by an interview. According to the result, the subject did not experience flow in the learning process, as likes he was in meditation. It happened because when he learned something, he felt be pressed by tasks. It’s important for individual to relax when they are learning.